KEANEKARAGAMAN JENIS MERANTI (Shorea spp.) PADA AREAL IUPHHK- HTI PT. BHATARA ALAM LESTARI KABUPATEN MEMPAWAH KALIMANTAN BARAT - Juniarti, Tri Kartika; Herawatiningsih, Ratna; Burhanuddin, . (JURNAL HUTAN LESTARI, 2017)
Diversity Of Meranti Species (Shorea spp.) In The IUPHHK-HTI Area PT. Bhatara Alam Lestari Mempawah Regency West Kalimantan. Meranti is a commercial tree species, meranti timber market is not limited only to domestic market but also international market, although meranti has become important commodity of forest product, but until now its production still relies on natural forest. The purpose of this research is to know the diversity of meranti species. The object of the study was the type of meranti (Shorea spp.) and the type of vegetation found in the observation plot. This research was conducted at IUPHHK-HTI area of PT. Bhatara Alam Lestari. Determination of plot and line of meranti species diversity in the field was using mixed method. The results showed that there are 4 types of meranti namely meranti batu, meranti bunga, meranti seraya and meranti sibo. The dominance index (C) at the growth rate of seedlings, saplings and trees has a low average value of less than 0.5, so it can be said that the spread of vegetation species is not concentrated in one particular species but spreads in all species. Result of Species Diversity (H) Compiler shows more than 1 (H 1 <H <3) value for all levels of vegetation growth means that species diversity (H) less than 1 (one) means species diversity in low or non-diverse transects. Result of Abundance (e) vegetation in general that Abundance of all growth rates of seedlings, saplings, poles and trees show the value (e) less than 1 means that all species are unequal abundance at each growth rate within a forest area.Keywords: Abundance, Diversity, Meranti.